Stylistic Analysis of Figurative Language at the ARTJOG 2025 Art Description Discourse - Ikvina Hasanatika; Muktar Garba (Jurnal Sastra Indonesia, 2026)
Discourse in art exhibitions serves as a communication bridge, translating visual ideas that are often abstract and polysemous. This research aims to describe the forms and connotative meanings of figurative language used in the descriptive discourse of the ARTJOG 2025 exhibition, "Motif: Amalan." This study employs a descriptive qualitative approach from a stylistic perspective. The research data consist of words, phrases, and sentences containing figurative language, collected through observation and note-taking from catalogs and artwork labels on the official ARTJOG 2025 website. Data analysis was conducted using the referential identity method based on Gorys Keraf's theory of figure of speech. The results show 16 instances of figurative language, including personification, metaphor, simile, and synecdoche. The dominance of personification (62.5%) indicates a curatorial effort to position artworks as active subjects capable of performing real actions, aligned with the exhibition's theme. The use of such figurative language plays a crucial role in transforming visual elements and the artists' complex philosophies into emotional narratives that are easily understood by the audience.